The evolution of cooperation in simple molecular replicators. Issue 1864 (11th October 2017) - Levin, Samuel R.; West, Stuart A.
Abstract : In order for the first genomes to evolve, independent replicators had to act cooperatively, with some reducing their own replication rate to help copy others. It has been argued that limited diffusion explains this early cooperation. However, social evolution models have shown that limited diffusion on its own often does not favour cooperation. Here we model early replicators using social evolution tools. We show that: (i) replicators can be considered to be cooperating as a result of kin selection; (ii) limited diffusion on its own does not favour cooperation; and (iii) the addition of overlapping generations, probably a general trait of molecular replicators, promotes cooperation. These results suggest key life-history features in the evolution of the genome and that the same factors can favour cooperation across the entire tree of life.